Analysis of Digital Technology and Effects on Human Resource Management Machine learning and its Diversity Equality Inclusion - K , Vishaal.; Lakshmi , Gundala Venkata Rama; Arumugam, Mahalaksmi; Selvi, Dr.K.; Nair, Rakesh Haridas; Indrapriya, Dr.M.; V, Revathi; Jarad, Dr. Rajendra Subhash; Kumar, S.Saravana (South Eastern European Journal of Public Health, 2024)
The digital technology significantly affects company management practices, necessitating adaptable changes. This study looks at how company HRM should change to keep up with the rapid advancement of digital technologies. The study's findings demonstrate how technology has impacted the labor market, the setting for businesses, and the number of jobs available. Human resource management is the foundation for digital empowerment and management transformation. Determine the particular biases in HR procedures that you want to target, such as age, gender, or ethnicity bias. Specify the goals you want to achieve, such as raising employee satisfaction, decreasing recruiting prejudice, and boosting diversity and inclusion metrics .Perform a comprehensive analysis of the body of research on bias in HR procedures, diversity and inclusion, and the use of machine learning to reduce bias.